2007
DOI: 10.2174/138527207781662500
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalysis in the Meerwein-Ponndorf-Verley Reduction of Carbonyl Compounds

Abstract: The Meerwein-Ponndorf-Verley (MPV) reaction involves the catalysed transfer of hydrogen from an alcohol to a carbonyl compound and provides an effective method for synthesizing carbonyl compounds under very mild conditions. The method, which requires the use of a catalyst, is high selective as it leaves most reducible functional groups in the carbonyl reactant untouched. The classical MPV reaction is conducted in a homogeneous phase, usually in the presence of a metal alkoxide as catalyst. The process has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…In general it has been stated that the reactivity of acrolein as the hydrogen acceptor from alcohols in the presence of MgO is very low compared to the reactivities determined for saturated carbonyl compounds [17,18,23,[27][28][29]. At 473 K the conversion of acrolein (results not shown) did not exceed 10%, whereas for saturated carbonyl compounds the conversions higher than 60% have been reported [17,18,23,27,29].…”
Section: Catalytic Activity Measurementsmentioning
confidence: 88%
See 1 more Smart Citation
“…In general it has been stated that the reactivity of acrolein as the hydrogen acceptor from alcohols in the presence of MgO is very low compared to the reactivities determined for saturated carbonyl compounds [17,18,23,[27][28][29]. At 473 K the conversion of acrolein (results not shown) did not exceed 10%, whereas for saturated carbonyl compounds the conversions higher than 60% have been reported [17,18,23,27,29].…”
Section: Catalytic Activity Measurementsmentioning
confidence: 88%
“…Metal oxides, MgO [11,12], ZrO 2 [13], double layered hydroxides [14], MgO-B 2 O 3 [15], and Al 2 O 3 -AlPO 4 [16] have been used as catalysts. According to literature data, MgO is one of the most active catalysts in CTH [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For the first two members of this set of ketoesters, namely ethyl pyruvate (1) and ethyl acetoacetate (2), a fast uptake of these esters with time was observed. Although for pyruvate (1) and acetoacetate (2), conversions as high as 89 and 97 % after 1 h of reaction were noted, no products were found in liquid mixtures collected during tests. It was shown that the direct reaction between the above-mentioned esters and MgO occurs with the formation of a salt-like product, which is responsible for their uptake.…”
Section: Characterization Of Mgo Catalystmentioning
confidence: 96%
“…Catalytic hydrogen transfer, also known as catalytic transfer hydrogenation (CTH), is a useful method for the reduction of many aldehydes and ketones to the corresponding alcohols under mild conditions [1,2]. This reduction can be performed either in vapor or liquid phase, depending on the acceptor reactivity, with alcohols as hydrogen donors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation